2009
DOI: 10.1007/s11515-009-0019-4
|View full text |Cite
|
Sign up to set email alerts
|

Season variability of iron effects on periodic culture of microalgae Dunaliella viridis Teod.

Abstract: Effects of different iron concentrations (final concentrations of iron in Artari's medium: 3.7, 37.0, 74.0, and 185.0 mmol$L -1 ) on growth rate and contents of protein, triacylglycerides, and β-carotene in Dunaliella viridis cells at cultivation in different months were investigated. It was shown that the dose-dependent effects of iron were notable for season variability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
2
2
0
Order By: Relevance
“…Although there are no studies on the influence of iron ions on carotenoid biosynthesis of acidophile microalgae, our results are in good agreement with the enhanced carotenoid accumulation published for other genera of microalgae; carotene accumulation has been shown to be enhanced in iron‐exposed Dunaliella species (Mojaat et al. 2008, Menzyanova et al. 2009).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Although there are no studies on the influence of iron ions on carotenoid biosynthesis of acidophile microalgae, our results are in good agreement with the enhanced carotenoid accumulation published for other genera of microalgae; carotene accumulation has been shown to be enhanced in iron‐exposed Dunaliella species (Mojaat et al. 2008, Menzyanova et al. 2009).…”
Section: Resultssupporting
confidence: 91%
“…3C), therefore revealing carotenogenesis stimulation. Although there are no studies on the influence of iron ions on carotenoid biosynthesis of acidophile microalgae, our results are in good agreement with the enhanced carotenoid accumulation published for other genera of microalgae; carotene accumulation has been shown to be enhanced in iron-exposed Dunaliella species (Mojaat et al 2008, Menzyanova et al 2009). Further studies on gene expression of the carotenoid biosynthesis pathway are being developed at our laboratory to determine the role played by iron in the enhanced biosynthesis of carotenoids.…”
Section: Optical Density Range 680 Nmsupporting
confidence: 91%
“…Similarly, Menzyanova et al. () reported that the IC in culture medium had an impact on cell growth and lipid content of Dunaliella viridis . An excess of metal, including iron, can lead to the formation of reactive oxygen species like hydrogen peroxide and other oxidant compounds (Miazek et al.…”
Section: Resultsmentioning
confidence: 89%
“…We are often faced with high variability of receiving β-carotene [21,22], microbial biomass yield [10,24], and the ambiguity of the obtained scientific results.…”
Section: Introductionmentioning
confidence: 99%